Compact 4-channel AWGs for CWDM and LAN WDM in data center monolithic applications. (December 2015) - Pan, Pan; An, Junming; Wang, Yue; Zhang, Jiashun; Wang, Liangliang; Qi, Ying; Han, Qin; Hu, Xiongwei
Abstract: InP-based 4-channel AWGs for Coarse Wavelength Division Multiplexing (CWDM) with channel spacing of 20 nm and Local Area Network (LAN) WDM with channel spacing of 800 GHz are designed and fabricated. The deep-ridge waveguide is used to make the chip compact, chip size of AWG for CWDM is 0.55×3.9 mm 2 and for LAN WDM is 1.6×3 mm 2 . The measured results indicate that, the insertion losses are −5 dB and −7 dB, crosstalk levels are below −25 dB and −24 dB for AWG with 20 nm channel spacing and 800 GHz channel spacing, respectively. These AWGs can be integrated with lasers and detectors array monolithically for data center applications. Highlights: Deep ridge waveguide is used to make chip size compact. The waveguide is designed polarization insensitively. The uniformity is optimized by considering dispersion. The measured response is matching well with the design value.